American cinematographers in the Great War, 1914-1918 - Castellan, James W.; Dopperen, Ron van; Graham, Cooper C., 1938- (John Libbey Publishing Ltd, 2016)
At the start of hostilities in World War I, when the United States was still neutral, American newsreel companies and newspapers sent a new kind of journalist, the film correspondent, to Europe to record the Great War. These pioneering cameramen, accustomed to carrying the Kodaks and Graflexes of still photography, had to lug cumbersome equipment into the trenches. Facing dangerous conditions on the front, they also risked summary execution as supposed spies while navigating military red tape, censorship, and the business interests of the film and newspaper companies they represented. Based on extensive research in European and American archives, American Cinematographers in the Great War, 1914-1918 follows the adventures of these cameramen as they managed to document and film the atrocities around them in spite of enormous difficulties.